(untitled) (Faridpur Medical College Journal, 2016)
Pancreatitis is a common non-bacterial inflammatory disease caused by activation, interstitial liberation and auto digestion of pancreas by its own enzymes. Common causes of acute pancreatitis are gall stones, alcohol, drugs, trauma, viral infections and hypertriglyceridemia. Much is known about the causes of pancreatitis but huge experimental data available about understanding of its pathogenesis is still incomplete. Hypercalcemia as a cause of pancreatitis is rarely reported. Hypercalcemia is usually the result of Primary hyperparathyroidism (PHPT) and the most common cause of PHPT is parathyroid adenoma. It is thought that the increased calcium concentration in pancreatic juice resulting from hypercalcemia may prematurely activate proteases. Mutations in different genes have been proposed as well to justify why only some patients with primary hyperparathyroidism and hypercalcemia develop acute pancreatitis. Here we present a case of recurrent acute pancreatitis resulting from hypercalcemia due to parathyroid adenoma in a 38-year-old man. Hyperparathyroidism was suspected when despite severe pancreatitis calcium level remained high and parathormone level was grossly raised Faridpur Med. Coll. J. Jan 2016;11(1): 36-38